Quantitative screening of geranylgeranoic acid in selected plant-based foods using LC/MS/MS - Yuki Tabata (Frontiers in Nutrition)
Geranylgeranoic acid (GGA), a bioactive acyclic isoprenoid, has been developed as a preventive agent against recurrent hepatocellular carcinoma. While previous studies have identified GGA in certain medicinal herbs, such as turmeric, its presence in other commonly consumed plant-based foods remains largely unexplored. In this study, we screened 14 plant-based food items using a validated LC/MS/MS method to quantify their GGA content. Among the tested samples, turmeric powder exhibited the highest GGA concentration (20.2 ± 8.25 ng/g dry weight), consistent with previous findings. GGA was also detected in several nuts, including almonds (Italy: 7.59 ± 2.45 ng/g; USA: 6.48 ± 1.28 ng/g), cashew nuts (4.12 ± 1.12 ng/g), and pistachios (3.48 ± 0.95 ng/g). Importantly, azuki beans (7.21 ± 2.12 ng/g) and soybeans (1.21 ± 0.29 ng/g) were also found to contain GGA, suggesting that some legumes may serve as additional dietary sources of this compound. In contrast, GGA was not detected above the limit of quantification for the following seven items: chickpea, walnut, sesame seeds, and dried parsley. These negative results are also informative for defining the boundaries of GGA distribution in plant-based foods. This study provides new data on the occurrence of GGA in plant-derived foods and contributes to a comprehensive understanding of its potential dietary sources.